Immune Thrombocytopenia in a Very Elderly Patient With Covid-19 - Hindilerden, Fehmi; Yonal-Hindilerden, Ipek; Sevtap, Senoglu; Kart-Yasar, Kadriye (Frontiers in Medicine, 2020)
Immune thrombocytopenia (ITP) is an autoimmune disorder characterized by a decreased number of platelets and mucocutaneous bleeding. Many viruses have been identified as triggers of the autoimmune process, including human immunodeficiency virus (HIV), hepatitis C virus (HCV), Epstein-Barr virus (EBV), cytomegalovirus (CMV), parvovirus, rubella and measles. Association with the new severe acute respiratory syndrome coronavirus, SARS-CoV-2 infection (Covid-19 infection) has been rarely reported. Here, we report the oldest case of ITP patient triggered by the novel coronavirus infection. He showed inadequate response to IVIG but responded to corticosteroids with no severe adverse events. Further studies are warranted to determine the optimal therapeutic strategies for ITP with the Covid-19 infection.